Water relations and photosynthetic responses of Kékfrankos grapevine (Vitis vinifera L.) in two terroirs with different ecological conditions - Zsófi, Zsolt; Bíró, Péter; Bálo, Borbála (Acta Biologica Szegediensis, 2005)
Behaviour of Kékfrankos (Vitis vinifera L.) grapevine in two terroirs (Eger-Nagyeged–hill and Eger-Kőlyuktető) were examined during the growing season 2003. There was a close relationship between physiological responses, yield, fruit quality and terroir environmental conditions. Lower water supply in Eger-Nagyeged-hill was detected during the season due to its sloping exposure and soil characteristics. Pressure-volume curves (PV-curves) indicated that there was no osmotic adjustment in the leaves of this variety. Higher osmotic concentration was measured in the leaves of the unstressed terroirs presumably due to higher photosynthetic activity. Differences in soil water content of the 2 terroirs resulted in altered cell wall elasticity of the Kékfrankos variety. Photosynthetic production per unit leaf area and total canopy surface was also affected by available soil water content being lower in Eger-Nagyeged-hill. Physiological distinction of the vines in the 2 terroirs resulted in altered yield and wine quality. Lower yield in Eger-Nagyeged-hill is partly connected to decreased photosynthetic production of the canopy. Improved wine quality of Eger-Nagyeged-hill is due to moderate water stress having positive effect at the end of the growing season and other microclimatic factors, i.e. elevated soil temperature and better sun exposure of leaves and clusters.